Understanding Communication and Identity Strategy of Indonesian Diaspora Women as YouTuber - Yusuf, Kurniawaty; Sudarmanti, Rini (Universitas Semarang, 2021)
Nowadays the presence of internet provides virtual spaces for diaspora women who are living outside Indonesia. Living within different cultures are challenging and social media platform can be as self-actualization medium to representing identities and expressing their emotional bonding with homeland. There are only several research which have revealed on how Indonesia women diaspora from mixed family especially in maintaining YouTube platforms. The aim of this study is tried to portray how Indonesian diaspora women revealing their national identity within video YouTube content. This research method was descriptive qualitative. Data were collected from ten videos of two Indonesian diasporas YouTuber who have mixed family, living abroad, and have more than 1 (one) million subscribers. We tried to explore from some categories such as video's location, moment or time background, target viewer, and on how delivering the messages within videos. Research finding showed that the video s contents indicated kind of negotiation construction for showing love and caring between homeland and recent locations, also acceptance with local identities. Elements of Indonesian are attached in their everyday life. In addition, they were still depicted as being related to domestic role and being responsible for taking care of the family.